1986
DOI: 10.1017/s0031182000063514
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus: absorption of cycloleucine and α-aminoisobutyric acid by protoscoleces

Abstract: Protoscoleces of Echinococcus granulosus absorb the amino acids cycloleucine and alpha-aminoisobutyric acid (AIB) by a combination of mediated uptake and diffusion. After correcting for the latter, values for Kt and Vmax of 0.124 mM and 0.947 nmoles/mg protein/2 min for cycloleucine were calculated; corresponding values for AIB were 0.039 mM and 0.139 nmoles/mg protein/2 min. Both amino acids were accumulated against a concentration gradient and a comparison of Kt and Ki values determined in mutual inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The uptake data derived from protoscoleces in these studies may thus reflect a combination of the permeability properties of both the evaginated scolex -neck of the presumptive adult worm and the soma of the protoscolex. Jeffs & Arme (1986) demonstrated the existence of membrane receptors for the transport of amino acids on protoscoleces. Active transport of cycloleucine and a-aminoisobutyrate (AIB) was shown and data suggested that both these amino acids shared a common uptake system.…”
Section: Echinococcus Granulosusmentioning
confidence: 99%
“…The uptake data derived from protoscoleces in these studies may thus reflect a combination of the permeability properties of both the evaginated scolex -neck of the presumptive adult worm and the soma of the protoscolex. Jeffs & Arme (1986) demonstrated the existence of membrane receptors for the transport of amino acids on protoscoleces. Active transport of cycloleucine and a-aminoisobutyrate (AIB) was shown and data suggested that both these amino acids shared a common uptake system.…”
Section: Echinococcus Granulosusmentioning
confidence: 99%
“…All materials and methods are as previously described by Jeffs & Arme (1986). Except where indicated, mean uptake is denoted by v, in units of nmoles/mg protein/2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1. Concentration ratios and post-absorptive metabolism {for details see text) Jeffs & Arme (1986). f AIB, a-aminoisobutyric acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations